Upaya Peningkatan Hasil Belajar Materi Kisah Teladan Fatimah Az-Zahra Dan Uwais Al-Qarni Melalui Metode Collaborative Learning Pada Mata Pelajaran Akidah Akhlak Kelas Xi Di Ma Yasni Sukaraja - Nurfatimah, Adisti; Taufik, Agung; Jaelani, Rijal; Sobariah, Yosa; Mubarok, Dasep Hanan (JURNAL MANAJEMEN PENDIDIKAN, 2025)
FATIMAH AZ-ZAHRA AND UWAIS AL-QARNI THROUGH COLLABORATIVE LEARNING  METHOD IN THE SUBJECT OF MORAL BELIEFS CLASS XI AT MA YASNI SUKARAJAThis study aims to determine the increase in learning motivation and learning outcomes through the Collaborative Learning model on the material of the exemplary story of Fatimah Azzahra and Uwais Alqarni in the subject of aqidah and akhlak for Class XI at MA YASNI. The model in this study uses the Kurt Lewin research model which is the main reference for various action research models. Data collection was carried out through observation, documentation and tests. Data analysis was carried out in 3 (three) stages including: data reduction, data presentation and drawing conclusions or verification. The subjects of this study were students in Class XI at MA YASNI in the 2024-2025 academic year, even semester, with a total of 21 students. Data collection techniques using interviews, observations, documentation, questionnaires, and written test assessments This study can find that the increase in learning outcomes through the Collaborative Learning learning model on the material of the exemplary story of Fatimah Azzahra and Uwais Alqarni in the subject of aqidah and akhlak Class XI at MA YASNI is the completion of student learning outcomes in cycle I reached 38,10% and increased by 52% to 90,48% in cycle II, with an average value in cycle I of 70,48% which increased by 15% to 85,24% in cycle II.